CONGENITAL HYPOTHYROIDISM - THE IMPORTANCE OF SCREENING AND TREATMENT OPTIMIZATION IN CHILDREN - Radosław Kuźma,; Adrianna Samoraj,; Jakub Zajączkowski,; Karolina Marrodán-Wojtczak,; Jan Wilk,; Kacper Stępniak,; Jakub Jarmołowicz,; Aleksandra Kujawa,; Karolina Krochmal,; Paulina Krzeszowska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Congenital hypothyroidism (CH) is an endocrine disorder that can lead to physical and cognitive impairment if not properly treated. The aim of this review is to discuss the importance of screening and treatment optimization in childhood, within the context of the healthcare system in Poland, with reference to European standards. The article also discusses the most important issues related to the topic of CH.Review methods: This article is based on a literature review from 2009 to 2025, with more focus put on papers published after 2017, analyzing national and international diagnostic, therapeutic guidelines, and long-term treatment outcomes. It also analyzes the challenges of differentiating permanent and transient forms and strategies for therapy monitoring.State of knowledge: Early diagnosis and treatment of CH (before 14th day of life) are crucial in preventing neurodevelopmental delays. Treatment involves lifelong thyroid hormone replacement therapy, but in cases of transient hypothyroidism, the withdrawal of the therapy at 2–3 years of age can be taken into consideration. Challenges in the topic of CH include diagnosing milder forms and personalizing treatment.Summary: Despite significant progress in CH diagnosis and treatment over the years, precise diagnosing and adjusting therapy to individual patient needs still remain a challenge. Future research should focus on developing better diagnostic tools, adjusting treatment to personal needs, and monitoring long-term neurodevelopmental outcomes among the pediatric population.